Status Ahli Waris Muslim Terhadap Harta Pewaris Non-Muslim Perspektif Yusûf Al-Qarḍâwî - Asadurrohman, Muhammad (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
The legal realignment of the inheritance in Indonesia was legally regulated through laws passed, such as KHI and KUHpdt. Whereas legally non-constitutional acts are in accordance with living laws. When it comes to inherited religious laws, it seems too sensitive to discuss in such a haphazard way that studies of semantics should be conducted. It is therefore intended to make thematic and scientific discussion efforts, so it is hoped that the result will be a soluble consideration for addressing the different religious legacies. As for the research method, the author uses is library research by making the maqâṣîd asy-Syarîʻah yusûf al-Qarḍâwî theory one of his basic analyses. From research it is understandable that yusûf al-Qarḍâwî held the right to inherit Muslim heirs to his non-muslim properties.